Proceedings of the 3rd Innovations in Theoretical Computer Science Conference 2012
DOI: 10.1145/2090236.2090275
|View full text |Cite
|
Sign up to set email alerts
|

Marginal hitting sets imply super-polynomial lower bounds for permanent

Abstract: Suppose f is a univariate polynomial of degree r = r(n) that is computed by a size n arithmetic circuit. It is a basic fact of algebra that a nonzero univariate polynomial of degree r can vanish on at most r points. This implies that for checking whether f is identically zero, it suffices to query f on an arbitrary test set of r + 1 points. Could this brute-force method be improved upon by a single point? We develop a framework where such a marginal improvement implies that Permanent does not have polynomial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The hypothesis of Theorem 1.7 bear some similarities with a result of Jansen and Santhanam [JS12] who showed that, for the class of univariate polynomial of degree d that are computable by small circuits, if there is a hitting set H of size d (any set of size d + 1 would have been sufficient) that can be efficiently encoded by a small TC 0 circuit, then Perm does not have polynomial sized constant-free algebraic circuits. Our hypothesis is similar in the sense that it requires a saving of one from the trivial hitting set for the appropriate class, but we only need the standard notion of explicitness for the hitting set.…”
Section: Relating Theorem 17 and Results Of Jansen And Santhanam [Jsmentioning
confidence: 64%
“…The hypothesis of Theorem 1.7 bear some similarities with a result of Jansen and Santhanam [JS12] who showed that, for the class of univariate polynomial of degree d that are computable by small circuits, if there is a hitting set H of size d (any set of size d + 1 would have been sufficient) that can be efficiently encoded by a small TC 0 circuit, then Perm does not have polynomial sized constant-free algebraic circuits. Our hypothesis is similar in the sense that it requires a saving of one from the trivial hitting set for the appropriate class, but we only need the standard notion of explicitness for the hitting set.…”
Section: Relating Theorem 17 and Results Of Jansen And Santhanam [Jsmentioning
confidence: 64%
“…One obvious task would be to improve the parameters of our result. As a matter of fact we have already obtained some preliminary results using a different framework involving high degree univariate polynomial identity testing [16]. Still, using low-degree multivariate polynomial identity testing as the target for derandomization may be easier, but there is the problem of connecting this up to lower bounds for permanent.…”
Section: Resultsmentioning
confidence: 99%
“…One very interesting technique which we have not yet been able to fit into the representationtheoretic framework and which is only partially uniform comes from Jansen and Santhanam [JS12,JS13]. The key property they use is the existence of Z hitting sets whose bit descriptions can be encoded by small uniform (or at least succinct [JS13]) circuits.…”
Section: Discussion Relation To the Gct Program And Future Directionsmentioning
confidence: 99%